Evaluation of play from private and public pre-school children's point of view - (:unkn) unknown (ELSEVIER SCIENCE BV, 2012)
Play is an activity that has different formats during childhood and adulthood. Therefore, it is investigated in different ways by those who are responsible for transforming children into individuals ready for the society, such as researchers, teacher or families. Finding out a child's perception of play as someone who actively engages in it would provide important source of data for families, teachers and researchers. The purpose of this study is to evaluate pre-school children's views on play. The sample consists of 40 pre-school children between the ages of 5-6 attending a preschool educational institution. Structured interviews were conducted to obtain children's views on play. The most significant finding from the qualitative analysis of children's statements was that lack of play was perceived as a negative emotional state by children. In addition, it is worth noting that children stated to play more at school than at home.
Keywords: point of view; preschool; children; play